Analisis Pengaruh Gaya Kepemimpinan, Budaya Organisasi, Lingkungan Kerja, Kompensasi Terhadap Motivasi Kerja Polisi Lalu Lintas Polresta Manado - Jan, Aritonang, Adolfina, (JURNAL RISET BISNIS DAN MANAJEMEN, 2018)
Work motivation is effect process or pushing a man to do for goal solution with expected. Culture of organization also important for rised in pushing motivation of employee work out of leadership style. This step because organization culture valued could to help employee work could to make a level motivation with amazing for employee to gave the best strongly in use opportunity gave by organization. Values with used together making employee feel enjoy to work, have commitment ang loyality making employeeÂ  better work, work increase and satisfied of employee work also keep competitive advantage. Â Keywords: Leadership style, Organization culture, Work motivation, Compensation, and work satisfied